Global research trends in zero-waste cities: a comprehensive bibliometric analysis - Han Wang; Bin Zhao; Shaban G. Gouda (Journal of Taibah University for Science)
Zero-waste cities are one of the important ways to promote resources sustainable development worldwide and have significant implications for promoting the recycling of waste resources and promoting global sustainable development. This study presents a comprehensive bibliometric analysis of zero-waste cities to explore the current research landscape. Web of Science Core Collection (WoSCC), PubMed and Scopus databases were used to retrieve a total of 392 articles containing research on zero-waste cities. These data were analysed by bibliometric methods to draw the research trends and recent advances in zero-waste cities comprehensive overview. The results show that the first article on zero-waste cities was published in 2008, marking the start of research in this area. In 2013, the most cited article was published by Zaman Au et al., and Italy is the country with the most research in this field. Additionally, the scholars and institutions who published the most papers in this field were investigated. Keywords: “circular economy”, “food waste”, “zero waste”, “recycling” and “waste management” remain the most used words in research. Furthermore, the data analysis illustrated that “waste collection” and its related components such as “waste diversion rate” and “waste generation” are emerging topics in zero-waste cities, however, it needs further development and more connections with zero-waste cities. Keywords such as “circular economy”, “sustainable development” and “carbon emissions” may become research hotspots or future trends. Finally, this study presents the future direction of zero-waste cities, thematic focus and research hotspots making a valuable contribution to zero-waste cities field.